THE PROVISION OF SUPPORT IN STUDENTS WITH SPECIAL NEEDS: TEACHER REFLECTION ON THEIR PRACTICE - Prudnikova, Ilga (Education Reform: Education Content Research and Implementation Problems, 2019)
Latvia is currently moving towards a competency-based approach to the curriculum, with the resultant need to update teacher professional competencies. A survey conducted by the project School 2030 in the second half of 2018 highlights the need for more personalised support to teaching/learning for each and every student. The teacher's capacity, therefore, to plan, prepare and lead the learning process is important.The question then arises: how to best support learning and effectively increase achievement for those learners with special needs. For the realisation of an inclusive approach to education, the teacher needs knowledge and understanding of the diverse needs of students, which need to be considered as part of the educational process.The aim of the study: to provide insight into diverse effective approaches to the education of students with special needs in inclusive settings.The research methods selected reflect the purpose of the study: analysis of regulatory documents, analysis of the scientific literature and teacher reflection on their practice.The main conclusion is that the provision of day-to-day support by competent teachers, as well as support at the educational institution level, results in students with special needs participating, being engaged, collaborating and achieving equally with the peers.This can only be achieved through the purposeful investment of hard and persistent work, utilising flexible learning opportunities and collaboration.